Pengembangan Digital Flipbook Kearifan Lokal Semarang untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Kelas IV Sekolah Dasar - Puspitasari, Ratih Kinanti; Irvan, Moh. Farizqo (Universitas Muhammadiyah Magelang, 2026)
This research is motivated by the low reading comprehension skills of fourth-grade students at SDN Sekaran 01. Initial observations indicate that some students have difficulty understanding the content of the reading, finding important information, and drawing conclusions from the texts they read. This condition is thought to be related to the learning process which is still dominated by lecture methods and has not been supported by the use of interesting and contextual learning media. As a result, student engagement in reading literacy activities is still not optimal. Therefore, innovative learning media are needed that can increase student interest and participation in reading activities. This study aims to develop a digital flipbook media based on Semarang local wisdom, determine the level of feasibility of the developed media, and test its effectiveness in improving elementary school students' reading comprehension skills. The method used in this study is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fourth-grade students of SDN Sekaran 01 in the 025/2026 academic year. The results of the study indicate that the digital flipbook media based on Semarang local wisdom has a very good level of feasibility. This is demonstrated by the validation results from material experts (93.8%) and media experts (93%), thus categorizing the theory as highly suitable for use in learning. Furthermore, the effectiveness test results indicated an increase in skills through the N-Gain test of 0.4957, which falls into the moderate category. Based on these findings, it can be concluded that the Semarang local wisdom digital flipbook has a high level of suitability and is quite effective in improving elementary school students' reading comprehension skills. In addition to supporting improved reading comprehension, this media also plays a role in introducing and instilling local wisdom values ​​in students through a more contextual and meaningful learning process.